PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Darmawati, Arum; Indartono, Setyabudi (Universitas Negeri Yogyakarta, 2015)
This study is aimed to explore the mediation effect of organizational commitment on the influence of job satisfaction on the organizational citizenship behavior. Respondent include on this study is the staff of Yogyakarta Sate University (YSU). Path analysis is used to analize the data. The result showed that organizational commitment is accepted to mediate the effect of job satisfaction on the organizational citizenship behavior. Hence organizational commitment is important for YSU staf to improve the effect of their job satisfaction on the organizational citizenship behavior.